Effect of Serotonin Concentration and Some Variables in the Sera 6 hours before and after Dialysis on Chronic Kidney Patients with Different Ages in Iraqi Population - Ahmed Chyad Abbas1 , Ahmed Zuhair Alwaeli2 , Ebtihal Chiad Abass3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
This study is concerned with chronic kidney disease and control group . The determine patients from (alsederhospital ) in Najaf city during the period between January 2019 to July 2019. The CKD patient and controlgroup consisted of sixty with age mean of (80 ±20) years. The blood samples were drawn from all patients 6hours before and after dialysis to measurement serotonin , blood Urea, Creatinine , uric acid and hemoglobinand control group. Also the patients classified into two groups according to age . This variables measured byusing assay (ELISA) technique and colorimetric methods. The higher mean value of serotonin was shownin CKD patients before dialysis ( 0.0257± 0.00224 ng /ml) compared with patients after dialysis ( 0.1894 ±0.05189 ng/ml) compared with control group( 0.0059 ± 0.00139 ng/ml). Also the higher value of blood Ureaand Creatinine reversibly in CKD patients before dialysis was (126.25± 4.869 mg/dL), (10.041± 0.3019mg/dL) compared in blood Urea and Creatinine in CKD patients after dialysis was (48.183± 2.262 mg/dL),(3.28± 0.201 mg/dL) and control group was (28.105 ± 1.896 mg/dL), (1. 095 ± 0.0961 mg/dL).Also the higher value of uric acid and hemoglobin reversibly in CKD patients before dialysis was (8.0623±0.1478 mg/dL), (13.800 ± 0.16519 g/dL) compared in uric acid and hemoglobin in CKD patients afterdialysis was (5.5361± 0.16055 mg/dL), (12.383 ± 0.15872 g/dL) and control group was (2.6789 ± 0.2977 mg/dL), (13.742 ± 0.18954 g/dL) , all above results there was a significant difference and correlation (p?0.05).Aim of study: Study the effect of serotonin, blood Urea, Creatinine , uric acid and hemoglobin 6 hoursbefore and after dialysis on CKD patients and compared with control group .Study the effect of variableson CKD patients with different age and study the relation between CKD patients after and before dialysis.